A current-source DC-AC converter and control strategy for grid-connected PV applications - Buzzio, Christian; Poloni, Yamil S.; Oggier, Germán G.; García, Guillermo O. (International journal of electrical power & energy systems, 2023)
•It is proposed a topology consisting of an input step-up stage, followed by a step-down stage and an unfolding inverter.•A decentralized control strategy of the DC-DC stage allows maximizing the renewable energy harvest and synthesizing an output current to be injected into the grid with low harmonic distortion.•The grid current controller proposed in this paper consists of a reduced number of resonant stages meeting the energy quality required by standards.•The article introduces a novel extension of a formerly presented design strategy for Proportional + Resonant controllers, to include harmonics compensation.•A 500 W prototype converter was implemented, and the experimental results show a fast transient response to step changes in both the input current and the phase angle reference. Also, the multi-resonant controller design presented in this article resulted in an injected current with a THD of 3.37%, compliant with the IEEE Std. 1547–2018. This paper presents a two-stage current-source DC-AC converter for grid-connected PV applications which is composed of an input step-up stage, followed by a step-down stage and an unfolding inverter. A decentralized control strategy of the DC-DC stage allows maximizing the renewable energy harvest using an Incremental Conductance MPPT algorithm and synthesizing an output current to be injected into the grid with low harmonic distortion. Double-loop PI controllers are used for the boost stage. The DC bus voltage of the buck stage is regulated using a PI controller, and an inner Proportional-Resonant (PR) controller tracks a sinusoidal reference. The PR controller proposed in this paper, includes a reduced number of resonant stages meeting the energy quality required by standards, which results in good stability margins. Finally, a SOGI-FLL algorithm synchronizes the inverter operation with the grid. Experimental results show an excellent dynamic response of the system, and the injected current complies with the IEEE Std. 1547–2018 specifications regarding harmonic content using a control law with a low computational burden.